The imbalance of relations between tax authorities and legal representatives in the tax court: An analysis of substantive justice and the constitutional guarantee of equality before the law - Akmal Suprobo (Journal of Law, Administration, and Social Science, 2026)
This study examines the implications of Constitutional Court Decision Number 26/PUU-XXI/2023 for the protection of human rights in tax dispute resolution in Indonesia, particularly concerning the principles of equality before the law and the right to a fair trial. This research employs a normative legal method using statutory, conceptual, and case approaches. The legal materials consist of legislation, court decisions, and relevant literature on human rights and the tax judiciary system. The findings indicate that prior to the decision, the Tax Court operated under a dual supervisory system involving both the Supreme Court and the Ministry of Finance. This arrangement created an imbalance between taxpayers and tax authorities, raising concerns regarding judicial independence and impartiality in tax dispute adjudication. Through Constitutional Court Decision Number 26/PUU-XXI/2023, the authority over the organizational, administrative, and financial supervision of the Tax Court was fully transferred to the Supreme Court. This institutional reform strengthens judicial independence and enhances the protection of the right to an independent, impartial, and fair hearing. Furthermore, the decision encourages broader reforms within the Tax Court system, including improvements to the licensing framework for legal representatives and greater transparency in judicial administration. Consequently, the decision represents a significant milestone in establishing a more equitable, independent, and human rights-oriented tax dispute resolution system in Indonesia.